(untitled) (American Journal of Interdisciplinary Research and Development, 2026)
Various socio-political movements in our history are important in the formation and maturation of the idea of national independence. One of such kind of political movement is the jadidism. In this article written about the content and essence, goals and objectives of the jadids’ a movement that arose in the Turkestan region in the late 19th and early 20th centuries. In particular, jadids’ work in bringing enlightenment and culture to a new level, their main idea were emphasized by the independence of the land, the liberation of the people. In the article, the author provides an analytical idea of which directions led in the early activities of jadidism, and then which areas of the cultural and educational front were covered. In the main part of the article, the main focus is on showing the place of jadids’ ideas in the process of our construction of today - New Uzbekistan. In particular, a hundred years have passed, to this movement, to the ideas that it has advanced, our President Sh. The fact that great attention is paid by Mirziyoev is explained on the basis of the principles of development of our today’s society. The author describes his comments on the basis of the congratulations of our president to the participants of the International Conference on the issues of jadidism and the views advanced in his speech at the expanded meeting of the Republican Council of spirituality and enlightenment. In the summary section of the article, the advanced ideas of the jadids show how relevant importance they have today in protecting the interests of society and the nation.